NaI(Tl) Detector Efficiency Computation Using Radioactive Parallelepiped Sources Based on Efficiency Transfer Principle - Mohamed S. Badawi; Mona M. Gouda; Ahmed M. El-Khatib; Abouzeid A. Thabet; Ahmed A. Salim; Mahmoud I. Abbas (Science and Technology of Nuclear Installations)
The efficiency transfer (ET) principle is considered as a simple numerical simulation method, which can be used to calculate the full-energy peak efficiency (FEPE) of 3″×3″ NaI(Tl) scintillation detector over a wide energy range. In this work, the calculations of FEPE are based on computing the effective solid angle ratio between a radioactive point and parallelepiped sources located at various distances from the detector surface. Besides, the attenuation of the photon by the source-to-detector system (detector material, detector end cap, and holder material) was considered and determined. This method is straightforwardly useful in setting up the efficiency calibration curve for NaI(Tl) scintillation detector, when no calibration sources exist in volume shape. The values of the efficiency calculations using theoretical method are compared with the measured ones and the results show that the discrepancies in general for all the measurements are found to be less than 6%.